MUHAMMAD QUTUB AND THE CONCEPT OF PUNISHMENT IN ISLAMIC EDUCATION - Ilyas, Ahmad Fauzi; Usiono, Usiono (LP2M IAI Al-Khairat Pamekasan, 2025)
The thoughts and concepts of punishment according to Muhammad Qutub are important to study, as he is one of the prominent figures in Islamic education who contributed significantly through his writings and activities as a lecturer at the Umm Al-Qura University in Mecca. This article raises this theme because there has been no research specifically discussing the concept of punishment in Islamic education according to Muhammad Qutub. The method used in this article is literature study, utilizing Muhammad Qutub’s book Manhaj Al-Tarbiyah Al-Islamiyah as the primary data source, along with relevant articles or books as secondary data sources. These data are analyzed through descriptive-interpretive analysis. This article finds that Muhammad Qutub’s concept of punishment is a form of sanction that can be applied in the process of Islamic education. While permissible, it is considered a last resort or an alternative measure when other methods do not work. Furthermore, the application of punishment should only be implemented after considering and understanding the physical and psychological conditions of the students.